2019
DOI: 10.3390/ijms20122912
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free, Embryo-Specific sncRNA as a Molecular Biological Bridge between Patient Fertility and IVF Efficiency

Abstract: Small noncoding RNAs (sncRNAs) are key regulators of the majority of human reproduction events. Understanding their function in the context of gametogenesis and embryogenesis will allow insight into the possible causes of in vitro fertilization (IVF) implantation failure. The aim of this study was to analyze the sncRNA expression profile of the spent culture media on day 4 after fertilization and to reveal a relationship with the morphofunctional characteristics of gametes and resultant embryos, in particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 63 publications
0
23
0
3
Order By: Relevance
“…Furthermore, The piRNAs have been found in spent culture media of embryo [59], our results shown that lots of piRNAs were present in porcine UFs-EVs. However, there are currently not enough studies on porcine piRNAs or effective methods that accurately predict their target genes in pigs, so this analysis of porcine UFs piRNAs is limited.…”
Section: De Mirnas Related To Proliferation Immunization and Angiogementioning
confidence: 54%
“…Furthermore, The piRNAs have been found in spent culture media of embryo [59], our results shown that lots of piRNAs were present in porcine UFs-EVs. However, there are currently not enough studies on porcine piRNAs or effective methods that accurately predict their target genes in pigs, so this analysis of porcine UFs piRNAs is limited.…”
Section: De Mirnas Related To Proliferation Immunization and Angiogementioning
confidence: 54%
“…However, collectively, the administration of exogenous gonadotropin led to substantial changes in the expression of these genes that play a crucial role in piRNA functions and biogenesis (Fig 1A and 1B). piR-NAs have strong effects on the occurrence of embryo implantation and they mediate the formation of healthy gametogenesis, especially in terms of genome integrity [5]. In a study, the purpose of which was to analyze the sncRNA expression profile of the spent culture media after fertilization and to investigate the relationship between the sncRNA and morphofunctional properties of gametes and the resulting embryos, it was revealed that some piRNAs have a significant effect on the occurrence of implantation, oocyte-cumulus complex and two pronuclei embryo numbers [40].…”
Section: Plos Onementioning
confidence: 99%
“…piR-NAs have strong effects on the occurrence of embryo implantation and they mediate the formation of healthy gametogenesis, especially in terms of genome integrity [5]. In a study, the purpose of which was to analyze the sncRNA expression profile of the spent culture media after fertilization and to investigate the relationship between the sncRNA and morphofunctional properties of gametes and the resulting embryos, it was revealed that some piRNAs have a significant effect on the occurrence of implantation, oocyte-cumulus complex and two pronuclei embryo numbers [40]. In other studies, it has been shown that abnormal conditions that cause defects in piRNA functions can lead to some important negative effects on the reproductive system, such as increased embryonic lethality [41] and infertility [19].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue contains eight original research studies [20,21,22,23,24,25,26,27], and five review papers [28,29,30,31,32]; the diversity of the papers demonstrates how many different topics are covered by cell-free nucleic acid research.…”
mentioning
confidence: 99%